Ardiente paciencia: uma dramaturgia possível - Sergio Parreiras Abritta (2024)
This dissertation is dedicated to investigating the relationship between literature and dramaturgy, in dialogue with the contemporary theatrical scene, based on the novel Ardiente paciencia ou El cartero de Neruda, by Antonio Skármeta. After the analysis of Skármeta's work, with the indication of the possible influences of the dramatic in its composition, as well as historically researched the periods related to the Brazilian coup of 1964 and Chilean coup of 1973, it went to the search, in the light of Didi-Huberman's studies on Aby Warburg's collection of images, for a dramatic language that would provide an approximation between these historical times, with the objective of pointing out, through the theater, possible similarities and differences between both, their developments and possible reflections in the recent anti-democratic movements occurred in Brazil. With the contribution of studies concerning the phenomenon of rewriting and research on contemporary dramaturgy, especially of Jean-Pierre Sarrazac and his concepts of rapsodic overflow and de-dramatization, theatrical poetics called lecture-performance has shown itself able to establish a dynamic dialogue between heterogeneous times and places and to promote a critical reflection on them. The text contained in the dissertation, elaborated within the language of the lectureperformance, was anchored in the juxtaposition of reports and images without any temporal or spatial linearity, with textual sequences assembled in a succession of autonomous moments, in the manner of the Warburgian atlas Mnemosyne. It was concluded that the lecture-performance artistic practice, uniting the discursive with the performative, contributed to the proposition of questions to the archives presented and to the audience, provoking the listening and contemplating the chance. It has also allowed the destabilization of the boundaries between the real and the fictional and the production of sensitive knowledge, which summons imagination more than reason.